Retiform Sertoli-Leydig Cell Tumor in a 38-Year-Old Woman: A Case Report, Retrospective Review, and Review of Current Literature - Laura C. Nwogu; Josh A. Showalter; Suvra Roy; Michael T. Deavers; Bihong Zhao (Case Reports in Pathology)
Ovarian sex cord-stromal tumors arise from the stromal cells that surround and support the oocytes. Sertoli-Leydig cell tumors belong to this category of ovarian neoplasms. We present the case of a 38-year-old woman who was found to have a right ovarian mass. The mass was resected and diagnosed as Stage I Sertoli-Leydig cell tumor, retiform variant, following histopathologic and immunohistochemical examination. This case is unusual given the rarity of the retiform variant of Sertoli-Leydig cell tumor and the atypically older age of 38 years at presentation.